Author Correction: Host-associated niche metabolism controls enteric infection through fine-tuning the regulation of type 3 secretion. Issue 1 (December 2018) - Connolly, James; Slater, Sabrina; O'Boyle, Nicky; Goldstone, Robert; Crepin, Valerie; Ruano-Gallego, David; Herzyk, Pawel; Smith, David; Douce, Gillian; Frankel, Gad; Roe, Andrew
The original version of this Article contained an error in the spelling of the author David Ruano-Gallego, which was incorrectly given as David R. Gallego. This has now been corrected in both the PDF and HTML versions of the Article.